Utility of molecular tools for the identification and characterization of infectious agents / Loong Shih Keng - Loong , Shih Keng (2020)
Molecular tools involving nucleic acid sequence-based detection offer rapid, sensitive and specific identification of bacterial infections, all together instrumental in timely patient management and infection control. Analyses of DNA sequences played a pivotal role in the discovery of novel or uncommon bacterial pathogens. This method can be applied to detect and identify rare and potentially pathogenic bacterial infectious diseases emerging from the interactions between human, animal and the environment. In this study, the 16S rDNA sequencing demonstrated superior utility against the conventional phenotypic identification systems for the identification of rare pathogenic bacteria. Its inability to differentiate between certain bacterial species however, was observed. For example, the 16S rDNA sequencing was unable to separate the non classical bordetellae. The 16S rDNA sequencing however, could serve as a primary molecular tool for the identification of bacterial pathogens at the genus level. Subsequent molecular analyses for specific bacterial identification and characterization require deeper genetic assessments such as utilizing the nrdA sequencing for bordetellae, multilocus sequence typing for Bordetella bronchiseptica, Burkholderia fungorum,Enterococcus faecalis and Escherichia coli, and determining ithe idraft igenome isequences for Kocuria marina. Additionally, structural analyses of ithe Tn1546 transposon of E.faecalis and E. igallinarum human clinical isolates revealed idistinct sequence variations that suggested possible nterspecies horizontal gene transfer events iin ithe ihospital. Findings from this study contributed indirectly to the eventual characterization of the novel bacterium, Bordetella pseudohinzii as this pathogen was initially named Bordetella genogroup 16. It was further noted that this bacterium was not confined only to laboratory rodents ias previously described, but also present in the wild rats. All laboratory rodent E. coli isolates turned out to be true commensals after testing negative for the presence iof antimicrobial and virulence genes, ensuring the reliability and reproducibility of research using these animals. Accurate identification of then opportunistic bacteria, B. fungorum and K. marina, and their association to the environment was made possible by using different molecular tools, highlighting the advantage of sequence-based methods to determine the source of infection. Overall, then 16S rDNA sequencing accomplished genus level identification of bacterial pathogens from various human, animal and environmental sources. Supplementing this method with other molecular tools and bacterial phenotypic assessments provided a multi dimensional specific identification mechanism to tackle the complexities involving the interactions between human, animal and environmental factors with emerging, opportunistic and rare bacterial pathogens.